The Urgency of Combating Human Trafficking for Online Scams in Indonesia - Bangun, Budi Hermawan; Kinanti, Fatma Muthia (Brawijaya Law Journal, 2025)
Human trafficking for online scams has emerged as a growing transnational crime, particularly in Southeast Asia. This study examines the role of ASEAN in combating this evolving form of human trafficking, highlighting its legal framework, challenges, and regional cooperation efforts. ASEAN has established multiple agreements, including the ASEAN Convention Against Trafficking in Persons (ACTIP) and the ASEAN Leaders' Declaration on Combating Trafficking in Persons Caused by the Abuse of Technology, to address the issue. However, the implementation of these agreements remains inconsistent due to the region’s adherence to the “ASEAN Way” principle, which prioritizes non-interference and consensus-based decision-making. This research employs a socio-legal approach, analyzing ASEAN’s institutional response and the legal framework supporting anti-trafficking measures. Findings indicate that while ASEAN has made significant strides in formalizing commitments, enforcement gaps persist. Human traffickers exploit weak border controls, technological advancements, and corruption to sustain their operations. Additionally, the rise of cyber fraud linked to trafficking in persons has intensified the urgency for coordinated regional action. The study underscores the need for ASEAN member states to adopt stronger enforcement mechanisms, improve victim protection, and enhance cross-border cooperation. Strengthening ASEAN’s role in combating human trafficking for online scams is crucial not only for upholding human rights but also for maintaining regional security and economic stability. The findings contribute to the discourse on transnational crime and the effectiveness of regional governance in addressing emerging criminal threats.